PENGARUH PENERAPAN ICE BREAKING TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV SDN PALMERAH 25 PAGI - Atiaturadiah, Nur; Rosyid, Ainur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning interest of students during the learning process in the classrom, especially in the subject of Natural and Social Sciences (IPAS). Students tend to feel easily bored, lack focus, and show little enthusiasm in participating in learning. These conditions have an impact on the low level of students’ participation and learning interest. One of the efforts that can be made to overcome this problem is by applying ice breaking. Ice breaking is a refreshing activity that can break the ice, build enthusiasm, and create is a pleasant learning atmosphere, so it is expected to increase students’ learning interest. The purpose of this study was to determine the effect of applying ice breaking on students’ learning interest in Natural an Social Sciences (IPAS) for fourth grade students at SDN Palmerah 25 Pagi. This research used a quasi-experimental method with a nonequivalent control group design. The participants consisted of two classes : an experimental group that received learning with ice breaking and a control group without it. A learning interest questionnaire was used as the research instrument, and the data were analyzed using a t-test. The results showed that the mean posttest score of the experimental class was 84,31, which was higher than the control class mean of 74,83. The t-test revealed a significance value of 0,000 < 0,05, indicating a significant difference between the two groups. Therefore, the application of ice breaking has a positive impact on improving students’learning interest in IPAS. Keywords: Ice Breaking, Learning Interest, IPAS